Learning Media Development Project Based on Demonstrative Tools - Zaki, Muhammad; Ali Ridho, Arsyad Muhammad (Ta'bir Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Ilmu Kebahasaaraban, 2024)
The abstract focuses on a "Learning Media Development Project Based on Demonstrative Tools," exploring the development and impact of educational media using demonstrative tools. The study aims to enhance teaching effectiveness through innovative media approaches in education. Qualitative document studies were employed to analyze existing educational practices and assess the integration of demonstrative tools. The research findings highlight the significant role of these tools in improving conceptual understanding and student engagement. By utilizing demonstrative tools, educators can create dynamic learning environments that foster interactive learning experiences. The impact of this approach is evident in its ability to facilitate clearer comprehension of complex concepts and enhance overall educational quality. In conclusion, the research underscores the importance of integrating demonstrative tools into educational practices to meet evolving learning needs and improve educational outcomes effectively